Lipid oxidation inhibition capacity of plant extracts and powders in a processed meat model system. (April 2020) - Burri, Stina C.M.; Ekholm, Anders; Bleive, Uko; Püssa, Tõnu; Jensen, Martin; Hellström, Jarkko; Mäkinen, Sari; Korpinen, Risto; Mattila, Pirjo H.; Radenkovs, Vitalijs; Segliņa, Dalija; Håkansson, Åsa; et al.
Abstract: A meat model system was used for screening lipid oxidation inhibiting capacity of diverse horticultural plant materials. In the model, heme-containing sarcoplasmic proteins from the meat water-phase were homogenized with linoleic acid and thiobarbituric reactive substances (TBARS) were measured. 23 Plant materials were investigated at three high (50, 100, and 200 ppm) concentrations and five plant extracts were tested at three low (5, 10, and 20 ppm) concentrations over time. In the high concentration sets, summer savory freeze-dried powder, beetroot leaves extracted with 50% ethanol, and an olive polyphenol powder extracted from wastewater, inhibited oxidation the most effectively. After two weeks and at 200 ppm concentration, oxidation was reduced to 17.2%, 16.6% and 13.5% of the blank sample with no added antioxidants respectively. In the low concentration set, spray dried rhubarb juice inhibited oxidation the most after two weeks at 5 ppm where oxidation was reduced to 68.3% of the blank sample with no added antioxidants. Highlights: A meat model resembling a processed meat product was proposed. Lipid oxidation was inhibited by most plant materials in this meat model. Great differences were found between plant powders and extracts. Beetroot leaf extract and olive waste water powder inhibited lipid oxidation most.